Strengthening Youth Capacity in English and Cultural Literacy through Contemporary Batik Design of Tapal Kuda Culture: Penguatan Kapasitas Pemuda dalam Bahasa Inggris dan Literasi Budaya melalui Pelatihan Desain Batik Kontemporer Berbasis Budaya Tapal Kuda - Ika Fitriani; Chandra Ayu Proborini; Diana Setia Dewi (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
This community service program is aimed to strengthen the capacity of youth members of Forum Pemuda Pelopor (FPP) Situbondo in English proficiency and cultural literacy, as well as to foster creativity through the development of contemporary batik motifs based on the local wisdom of the Tapal Kuda region. The program was based on the result of need analysis revealed that > 65% of FPP members had difficulties in all aspects of English skills, and >60% had limited knowledge of local culture. To address these issues, a series of 10 training sessions were conducted combining synchronous and asynchronous English learning, self-access language learning, and hands-on cultural activities. Results indicate a significant improvement: 89% of participants reported have better English and cultural literacy skills. The program highlights the relevance of integrating language learning with local culture and creative hands-on activities, while also providing a replicable model for sustainable youth empowerment.